2021
DOI: 10.1002/gea.21845
|View full text |Cite
|
Sign up to set email alerts
|

An oasis soil reference collection for the identification and study of ancient cultivated soils in arid environments (Oasis of Masafi, United Arab Emirates)

Abstract: Oasis soils result from the combined action of natural and anthropic processes, and thus constitute valuable systems for the understanding of human–environment trajectories over the millennia. The present research aims to develop the study of ancient oasis soils by identifying proxies to detect past agricultural practices. Ten reference pits were dug in Masafi, in both cultivated plots (irrigated plots with palm trees/fruit trees/cereals; manure/ashes/carbonates) and abandoned ones. Bulk sediment samples were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 62 publications
1
2
0
Order By: Relevance
“…The EC data showed that soils of abandoned plots in the Metouia Oasis were ch acterized as highly saline. Our results are consistent with those of Costa et al [5], w reported extremely high values of salinity in abandoned soils of the oasis of Masafi in United Arab Emirates. Gopalakrishnan and Kumar [6] also reported extremely sal soils in permanently abandoned paddy lands in the semi-arid region of the Jaffna P insula, Sri Lanka.…”
Section: Discussionsupporting
confidence: 94%
“…The EC data showed that soils of abandoned plots in the Metouia Oasis were ch acterized as highly saline. Our results are consistent with those of Costa et al [5], w reported extremely high values of salinity in abandoned soils of the oasis of Masafi in United Arab Emirates. Gopalakrishnan and Kumar [6] also reported extremely sal soils in permanently abandoned paddy lands in the semi-arid region of the Jaffna P insula, Sri Lanka.…”
Section: Discussionsupporting
confidence: 94%
“…To combat soil erosion and degradation, oasis farmers implement soil conservation measures such as terracing, contour bunding, and agroforestry. These practices help stabilize soils, retain moisture, and improve soil structure (Costa et al, 2021;Yang et al, 2021).…”
Section: Soil Conservation and Organic Farming 8641 Soil Conservation...mentioning
confidence: 99%
“…Some efforts have also been made to develop models to quantify pedogenetic trends associated with environmental change (e.g., Yaalon, 1975;Sheldon and Tabor, 2009). An essential application of paleopedology has been devoted to solving archaeological problems, as soils can be considered repositories of human activities: agriculture, forestry, material for construction or ceramic production, dwelling and householding (Holliday, 2009;Costa et al, 2021;Yalçın et al, 2021).…”
mentioning
confidence: 99%